PENGARUH LEADER MEMBER EXCHANGE, EMPOWERMENT, TALENT MANAGEMENT TERHADAP TURNOVER INTENTION - I Komang Gede; Milla Permata Sunny (Widya Manajemen, 2019)
The purpose of this study to examine the influence of leader member exchange, empowerment, talent management to turnover intention on employees of PT Bank BRI Cabang Gatot Subroto. Sample used as many as 55 people with census method (total sampling), the analysis technique used is multiple linear regression. The result of analysis is known that member exchange leader has positive and significant impact to employee intention turnover at PT Bank BRI Cabang Gatot Subroto. Empowerment has a negative and significant effect on employee intention turnover at PT Bank BRI Cabang Gatot Subroto. Talent management has a negative and significant effect on employee intention turnover at PT Bank BRI Cabang Gatot Subroto. Suggestions for management conduct discussions led by employers with employees to deal with problems that occur in the company, as the company's leadership should teach employees to work smart and fast by teaching a good work culture so that employees work again with enthusiasm. Companies must continue to develop talent management as a foundation for educating and developing employee talents. The management of PT Bank BRI Cabang Gatot Subroto in facing the problem of employee turnover intention is much influenced by the level of education, this need to be evaluated by the management and the leader in the future in order to be able to give place to the employee so as to be able to suppress the turnover intention.